Ahlul Bayt Perspektif Syiah dan Sunni: Studi Tafsir Al-Mîzan dan Tafsir Tahrîr wa Al-Tanwîr - Musolli Musolli (Universitas Nurul Jadid, 2017)
This article attempts to verify that every interpreters have different kinds of interpretation based on their own ideologies. The different exegesis on Surah al-Ahzâb (33): 33 makes it justified. The school of Sunni maintains that Ahlul Bayt is not merely limited to Ahlul Kisa’ as coined among proponents of the school of Shi’i. furthermore, related to the in-deepth investigation of using al-asbâb al-nuzûl of the Surah, it seems to be concluded that Ahlul Bayt in that verse is Ali’s members of family, including Ali, Fatimah, Husain, Hasan, and Prophet Mohammad. At least this is the core of result of the investigation to which this article tries to achieve.